2020
DOI: 10.1080/17512786.2020.1771753
|View full text |Cite
|
Sign up to set email alerts
|

Tweeting Outside the Lines: Normalization and Fragmentation as Political Reporters Break from the Mainstream

Abstract: The field of journalism is experiencing intense diversification in form and message while trying to overcome widespread public disaffection by reinforcing professional norms. This study focuses on two forces-normalization and fragmentation-by observing them at work on social media. We analyzed content and interactions from mainstream and non-mainstream political journalists covering a 2016 U.S. presidential debate. Forces of normalization would draw these two groups of reporters together in a monolithic, wides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(44 reference statements)
1
5
0
Order By: Relevance
“…Next, we found that the foreign correspondents tended to interact with each other and local journalists on Twitter far more frequently than with those outside their professional circle, thereby corroborating previous research (Molyneux & Mourão, 2019). This preference suggests that the correspondents were forming an interpretive community with other journalists on Twitter, the purpose of which was to share information with their audiences rather than to invite members of the public to contribute to the news production processes (Mourão, 2015;Mourão & Molyneux, 2020). Furthermore, the findings revealed that tweets containing foreign correspondents' personal opinions encouraged more audience engagement.…”
Section: Discussionsupporting
confidence: 85%
“…Next, we found that the foreign correspondents tended to interact with each other and local journalists on Twitter far more frequently than with those outside their professional circle, thereby corroborating previous research (Molyneux & Mourão, 2019). This preference suggests that the correspondents were forming an interpretive community with other journalists on Twitter, the purpose of which was to share information with their audiences rather than to invite members of the public to contribute to the news production processes (Mourão, 2015;Mourão & Molyneux, 2020). Furthermore, the findings revealed that tweets containing foreign correspondents' personal opinions encouraged more audience engagement.…”
Section: Discussionsupporting
confidence: 85%
“…Domestic governmental new media research mostly takes Weibo, WeChat, and TikTok as research platforms (Gu, Min, & Zhan, 2018;Xu, 2020;Zhou, 2019;Li, 2022). In contrast, foreign governmental new media research mainly uses Twitter and Facebook as research or data acquisition platforms (Mourão & Molyneux, 2021;Brandt et al, 2020;Tian & Yang, 2022;Mohd Fathir, Mohd Lokman, Abd Kadir, & Sualman, 2022;Sahly, Shao, & Kwon, 2019). The common denominator is that the proportion of video platform-related studies is on the rise, which is in line with the changes in the layout of government platforms and the rising trend of short videos.…”
Section: Discussionmentioning
confidence: 99%
“…Cross-platform studies still need to be included. Most studies on news content and audience engagement have been conducted using the content analysis method (Gu, Min, & Zhan, 2018;Mourão & Molyneux, 2021;Cushion, Morani, Kyriakidou, & Soo, 2021;Tian & Yang, 2022;Mohd Fathir, Mohd Lokman, Abd Kadir, & Sualman, 2022;Sahly, Shao, & Kwon, 2019), which is a single method that can verify the regression relationship between content attributes and audience engagement. Only one article used the experimental method (Janét, Richards, & Landrum, 2020), one article used the case study method (Brandt et al, 2020), and one article used interviews (Mihelj, Kondor, & Štětka, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly regarding political news, the news organizations were found to rely heavily on politicians and media as news sources. Mourão and Molyneux (2020), in their study of how political reporters in mainstream and non-mainstream outlets in the United States covered on Twitter the first presidential debate in 2016, found out that mainstream journalists essentially reinforced their role as gatekeepers by predominantly using as sources or by interacting with other journalists instead of other actors outside the mainstream media field. Several other studies have also shown that journalists mainly interact with their colleagues on their Twitter accounts and tend to predominantly retweet content published by other journalists and media outlets (Nuernbergk 2016;Folker and Nölleke 2019;Bentivegna and Marchetti 2018).…”
Section: Sourcing and Framing Journalistic Norms And Practices In Thementioning
confidence: 99%